Biochanin A, a Phytoestrogenic Isoflavone with Selective Inhibition of Phosphodiesterase 4, Suppresses Ovalbumin-Induced Airway Hyperresponsiveness. (14th March 2011) - Ko, Wun-Chang; Lin, Ling-Hung; Shen, Hsin-Yi; Lai, Chi-Yin; Chen, Chien-Ming; Shih, Chung-Hung
Abstract : The present study investigated the potential of biochanin A, a phytoestrogenic isoflavone of red clover ( Triflolium pratense ), for use in treating asthma or chronic obstructive pulmonary disease (COPD). Biochanin A (100 μmol/kg, orally (p.o.)) significantly attenuated airway resistance (R L ), enhanced pause (P enh ), and increased lung dynamic compliance (C dyn ) values induced by methacholine (MCh) in sensitized and challenged mice. It also significantly suppressed an increase in the number of total inflammatory cells, neutrophils, and eosinophils, and levels of cytokines, including interleukin (IL)-2, IL-4, IL-5, and tumor necrosis factor (TNF)-α in bronchoalveolar lavage fluid (BALF) of the mice. However, it did not influence interferon (IFN)-γ levels. Biochanin A (100 μmol/kg, p.o.) also significantly suppressed the total and ovalbumin (OVA)-specific immunoglobulin E (IgE) levels in the serum and BALF, and enhanced the total IgG2a level in the serum of these mice. The PDE4H /PDE4L value of biochanin A was calculated as >35. Biochanin A did not influence xylazine/ketamine-induced anesthesia. Biochanin A (10 30 μM) significantly reduced cumulative OVA (10 100 μg/mL)-induced contractions in the isolated guinea pig trachealis, suggesting that it inhibits degranulation of mast cells. In conclusion, red clover containing biochanin A has the potential for treating allergic asthma and COPD.